The Southern Wildlife Watcher : Notes of a Naturalist - Simbeck, Rob (Book collections on Project MUSE., 2020)
"The joys and mysteries of wildlife are all around us-if only we would take a moment to stop, look, and listen. These heartfelt and informative and witty reflections by award-winning journalist and author Rob Simbeck, accompanied by stunning color photographs, open our eyes to creatures large and small, common and uncommon, drab and flashy, routine and mysterious. Simbeck sings the praises of the fox and the frog, the shark and the spider, the owl and the oyster, providing a "personality profile" as well as natural history of these species found in the Southern quadrant of the United States. Each piece is lyrical and descriptive, with Simbeck's informal anecdotes supplemented by insights from naturalists and wildlife experts. The book is divided into three parts: animals in the air, land, and water. Each reflection includes a quick reference with a description of each animal, its habitat and range, and viewing tips. (The best place to view the Great White Shark is on your television!) Legendary author and photographer Jim Casada provides a foreword"--